2013
DOI: 10.1002/ptr.5094
|View full text |Cite
|
Sign up to set email alerts
|

Acute, Reproductive Toxicity and Two‐generation Teratology Studies of a Standardized Quassinoid‐rich Extract of Eurycoma longifolia Jack in Sprague–Dawley Rats

Abstract: The roots of Eurycoma longifolia Jack are popularly sought as herbal medicinal supplements to improve libido and general health amongst the local ethnic population. The major quassinoids of E. longifolia improved spermatogenesis and fertility but toxicity studies have not been well documented. The reproductive toxicity, two generation of foetus teratology and the up-and-down acute toxicity were investigated in Sprague-Dawley rats orally treated with quassinoid-rich E. longifolia extract (TAF273). The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…The oral median lethal dose (LD 50 ) of a similar quassinoid-rich E . longifolia extract for female and male Sprague-Dawley rats was 1293 and > 2000 mg/kg, respectively [ 53 ]. In the same study, normal prostate histology with the absence of hyperplasia was also observed in tissues of rat fed chronically with the extract.…”
Section: Discussionmentioning
confidence: 99%
“…The oral median lethal dose (LD 50 ) of a similar quassinoid-rich E . longifolia extract for female and male Sprague-Dawley rats was 1293 and > 2000 mg/kg, respectively [ 53 ]. In the same study, normal prostate histology with the absence of hyperplasia was also observed in tissues of rat fed chronically with the extract.…”
Section: Discussionmentioning
confidence: 99%
“…Though EN (14.49 ± 0.26% w/w) was about two fold higher than EP (7.39 ± 0.17% w/w) in concentration from the original TAF2 extract, the AUC 0-24 and F abs data (Table 1B) showed a 3.3 fold higher increment of blood EN than EP concentrations produced by the formulated TAF2-SD. From the previously reported data, EN was relatively less polar than EP, since the latter developed a shorter retention time than EN in the reverse phase HPLC chromatogram [22], and a smaller R f value than EN on TLC of normal phase silica gel coated plates [23]. Furthermore, the structures of both quassinoids (Figure 1) are the same except the epoxide moiety in EP, whereas EN displayed a double bond at C-13 and C-21.…”
Section: Discussionmentioning
confidence: 77%
“…The reference quassinoid markers of eurycomanone (EN) and 13α(21)-epoxyeurycomanone (EP) were isolated and purified from the TAF2 extract following previously described protocol [22]. The spectroscopic data (UV, IR, MS and NMR) of the two quassinoids were similar to those previously reported [23]. The purity of the quassinoids was above 95% as determined by a Waters Delta Prep HPLC system equipped with a Waters 2996 photodiode array detector (PDA) and Empower 2 workstation (Waters, Milford, MA).…”
Section: Methodsmentioning
confidence: 76%
See 1 more Smart Citation
“…Fertility was estimated in adult male Wistar rats according to the method of Pandey et al 14 24 h after 28 days MEPA, each male was placed in a separate cage with two virgin untreated female of the same strain. They are left together for 7 days, and during this period, one estrous cycle should have elapsed as described by Low et al 15 Following positive identification of mating, female were placed to individual cages. Positive mating was confirmed by the presence of a copulatory plug or the presence of sperm in the vaginal smears.…”
Section: Examination Of Male Fertilitymentioning
confidence: 99%